Low-gram-weight coated paper and application thereof in cigarette carton packaging

By using wood powder and a coating containing microcapsules in the cigarette box wrapping paper, a network structure is formed, which solves the problem of insufficient stiffness of the cigarette box wrapping paper, and achieves better protection effect and cost reduction.

CN119593256APending Publication Date: 2025-03-11HUBEI CHINA TOBACCO INDUSTRY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411988723.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing cigarette box packaging paper is not stiff enough to effectively protect the small cigarette pack, and it is costly and has environmental problems.

Method used

Low gram weight coated paper, including paper substrate and coating, the paper substrate contains wood powder, the coating contains microcapsules with shells of urea formaldehyde resin, core bodies are epoxy resin, and binders, and these components are used to form a network structure with rigid support points.

Benefits of technology

The rigidity of composite paper is significantly improved, making it suitable for cigarette cartridge packaging, which can maintain the regular and three-dimensional appearance of the cartridge, and effectively protect the inner small cigarette pack, while reducing costs and improving environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223170710000091
    Figure BDA0005223170710000091
Patent Text Reader

Abstract

The invention relates to the technical field of cigarette packaging, in particular to low-gram-weight coated paper and application of the low-gram-weight coated paper in cigarette carton packaging. The low-gram-weight coated paper comprises a paper substrate and a coating arranged on at least one surface of the paper substrate, a material for forming the paper substrate comprises wood flour; materials for forming the coating comprise microcapsules and a binder, shells of the microcapsules comprise urea resin, and cores of the microcapsules comprise epoxy resin. According to the invention, wood flour in a paper substrate, a shell in a coating comprising urea resin and a core comprising microcapsules of epoxy resin are utilized to synergistically obtain a network structure with rigid supporting points, and the network structure with the rigid supporting points is helped to be uniformly infiltrated in the paper substrate in cooperation with the use of a binder; therefore, the paper-plastic composite paper with better stiffness is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cigarette packaging, and in particular to a low-weight coated paper and application thereof in cigarette carton packaging. Background Art

[0002] The packaging method of cigarette cartons is: first arrange the small boxes in a "two-five" pattern; then use the carton label paper to wrap the arranged small boxes to form a carton; finally wrap a layer of transparent paper outside the carton and heat seal it. Among them, the carton label paper usually uses white cardboard, which has the characteristics of high stiffness, strong burst resistance, good smoothness and high whiteness, and is very suitable for printing and packaging, but it also has the problem of high cost; and the use of transparent paper (film) also has certain environmental problems. In order to reduce costs, increase efficiency and be green and environmentally friendly, it is urgent to provide a new packaging paper to replace white cardboard and transparent paper and use it as carton label paper.

[0003] At present, there is no research on new packaging paper in the field of cigarette box packaging. In other packaging fields, paper-plastic structure packaging has been developed, which has the advantages of good barrier properties and recyclability, and has been widely used. For example, a patent document with publication number CN117980561A discloses such a coated paper product, including: a paper substrate including a first side and a second side; a first coating on the first side of the paper substrate, wherein the first coating includes ethylene-acrylic acid (EAA) or vinyl acetate acrylate copolymer (VAcA) or styrene-acrylate (SA) or acrylic latex; and a second coating on the first coating, wherein the second coating includes EAA and talc, and wherein the dry weight ratio of EAA to talc in the second coating is between 100:5 and 100:70. The paper substrate is machine glazed (MG) kraft paper or machine polished (MF) kraft paper. Used to wrap products, such as flow wrapping products in sealable paper bags, such as gusset bags or pillow bags, in e-commerce packaging, in bedding packaging, such as pillow wraps, or in tissue paper wraps.

[0004] This type of coated paper is mainly suitable for bag-type packaging and is used to package products that do not have a regular three-dimensional shape. However, it is not suitable for cigarette box packaging, mainly because of its low stiffness. When it is used as a cigarette box, it will become soft and wrinkled due to insufficient stiffness, and it cannot protect the small cigarette packs inside well. Summary of the invention

[0005] The present invention aims to solve the above problems and provides a low-weight coated paper with low cost, high stiffness and suitable for cigarette carton packaging and its application in cigarette carton packaging.

[0006] The technical solution to the problem of the present invention is, first, to provide a low-weight coated paper, including a paper substrate and a coating arranged on at least one side of the paper substrate; the material forming the paper substrate includes wood powder; the material forming the coating includes microcapsules and a binder, the shell of the microcapsule includes urea-formaldehyde resin, and the core includes epoxy resin.

[0007] In the present application, by adjusting the components of the paper matrix and the coating, the cost is reduced and the stiffness of the composite paper (coated paper) formed by the two is synergistically improved. The specific principle is speculated as follows: first, the paper matrix contains wood powder, which is mainly composed of cellulose, hemicellulose, lignin and other components. In terms of cost, wood powder can be derived from a large amount of scraps generated during wood processing. By replacing part of the pulp with wood powder, the cost of papermaking can be reduced. In terms of stiffness, wood powder can fill the gaps in pulp fibers, making the fiber structure of the paper more compact and preliminarily improving the stiffness of the paper matrix; at the same time, wood powder contains a large number of polar groups such as hydroxyl and methoxy groups, which are used for subsequent synergistic effects with the coating. Secondly, the coating contains microcapsules with a shell including urea-formaldehyde resin and a core including epoxy resin. The urea-formaldehyde resin of the shell has more polar groups such as epoxy and hydroxyl groups, which can react with the polar groups such as methoxy and hydroxyl groups in the above-mentioned wood powder at high temperature of heat sealing to form hydrogen bonds, thereby forming an interpenetrating network, which not only ensures the combination of the coating and the paper matrix, but also the network structure can evenly extend the external tension to all parts through the hydrogen bond force, so that the compression resistance of the composite paper is enhanced and it will not break, and the stiffness of the composite paper is improved; and the epoxy resin of the core has a rigid structure, forming a support point in the network structure. When the composite paper is under pressure, the rigid molecules in the network structure can support the network system and resist the external force, so that the paper will not be crushed, and the stiffness of the composite paper is further improved. Finally, the coating contains a binder, which is convenient for heat sealing after the composite paper is packaged, and on the other hand, the binder helps the microcapsules to be evenly dispersed and infiltrated into the paper matrix, ensuring that the network structure with rigid support points is formed and evenly dispersed in the composite paper. Based on this, the technical solution of this application is completed.

[0008] In the material forming the paper matrix, the amount of wood powder is not limited, but an appropriate amount can further improve the performance of the composite paper. For example, too little wood powder may affect the formation of the network structure in the composite paper, and too much wood powder may affect the physical properties of the paper matrix. As a preferred embodiment of the present invention, the amount of wood powder added to the material forming the paper matrix is ​​10-20wt%, such as 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, preferably 15wt%.

[0009] The wood powder can be ordinary wood powder or modified wood powder, and the modification method can be esterification modification, etherification modification, cationic modification, etc. As a preferred embodiment of the present invention, the wood powder is cationized modified wood powder. After cationization, the wood powder is positively charged and can form ionic bonds with negatively charged pulp fibers, thereby promoting the retention of the wood powder and increasing the fiber connection strength.

[0010] The method of cationization modification of wood powder is not limited, for example, a cationic etherifying agent can be used for modification. In some embodiments, 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) is used to replace the quaternary ammonium salt group of the hydroxyl group on the wood powder to achieve the cationization of the wood powder. As a preferred embodiment of the present invention, the 3-chloro-2-hydroxypropyltrimethylammonium chloride and the wood powder are mixed in a mass ratio of (10-20):100 and reacted at a pH of 11-13 and a temperature of 60-80°C for 3-5h. Among them, the mass ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to wood powder can be 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100, 20:100, preferably 15:100. The pH may be 11, 12, 13, preferably 12. The temperature may be 60° C., 65° C., 70° C., 75° C., 80° C., preferably 70° C. The reaction time may be 3 h, 3.5 h, 4 h, 4.5 h, 5 h, preferably 4 h.

[0011] Among the materials forming the paper matrix, the components other than wood powder can be common components for papermaking, such as wood pulp, straw pulp, bamboo pulp, waste paper pulp, chemical pulp, mechanical pulp, semi-chemical pulp, etc. As a preferred embodiment of the present invention, the material forming the paper matrix also includes waste paper pulp to further reduce the cost.

[0012] The specifications of the paper substrate are not limited, but appropriate specifications are more conducive to maintaining stiffness and protecting the small cigarette pack while reducing costs. For example, if the basis weight, thickness and tightness of the paper substrate are too high, it may increase costs, and if the tightness is too high, it may affect the wetting effect of the coating in the paper substrate; if the basis weight, thickness and tightness of the paper substrate are too low, it will lead to insufficient stiffness and affect the packaging protection effect. As a preferred embodiment of the present invention, the basis weight (gram weight) of the paper substrate is 45 to 55 g / cm 2 , belongs to low-weight paper, the quantitative can be 45g / cm 2 , 46g / cm 2 , 47g / cm 2 , 48g / cm 2 , 49g / cm 2 , 50g / cm 2 , 51g / cm 2 , 52g / cm2 , 53g / cm 2 , 54g / cm 2 , 55g / cm 2 , preferably 50g / cm 2 .

[0013] As a preferred embodiment of the present invention, the thickness of the paper substrate is 60-80μm, for example, it can be 60μm, 61μm, 62μm, 63μm, 64μm, 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 79μm, 80μm, preferably 70μm.

[0014] As a preferred embodiment of the present invention, the density of the paper substrate is 0.65-0.80 g / cm 3 , for example, it can be 0.65g / cm 3 , 0.66g / cm 3 , 0.67g / cm 3 , 0.68g / cm 3 , 0.69g / cm 3 , 0.7g / cm 3 , 0.71g / cm 3 , 0.72g / cm 3 , 0.73g / cm 3 , 0.74g / cm 3 , 0.75g / cm 3 , 0.76g / cm 3 , 0.77g / cm 3 , 0.78g / cm 3 , 0.79g / cm 3 , 0.8g / cm 3 , preferably 0.7 g / cm 3 .

[0015] In the material forming the coating, the amount of microcapsules is not limited, but the appropriate amount can further improve the performance of the composite paper. For example, too little microcapsules may affect the formation of the network structure in the composite paper, and too much microcapsules may cause insufficient bonding of the composite paper and increase the formaldehyde content of the composite paper. As a preferred embodiment of the present invention, the amount of the microcapsules added to the material forming the coating is 5 to 10wt%, such as 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, preferably 7.5wt%.

[0016] The shell of the microcapsule may include only urea-formaldehyde resin, or may include urea-formaldehyde resin and other components that can further form hydrogen bonds with wood powder or improve the performance of urea-formaldehyde resin. As a preferred embodiment of the present invention, the shell of the microcapsule also includes lignin. Lignin is an amorphous three-dimensional network aromatic macromolecule that can form hydrogen bonds with wood powder and can also undergo hydroxymethylation reaction with free formaldehyde in urea-formaldehyde resin, which can not only reduce the formaldehyde content but also increase the mechanical properties of urea-formaldehyde resin in terms of elastic modulus. In this embodiment, as a preferred embodiment of the present invention, the mass ratio of urea-formaldehyde resin to lignin is 100:(1-5), for example, it can be 100:1, 100:2, 100:3, 100:4, 100:5, preferably 100:3.

[0017] The core of the microcapsule may include only epoxy resin, or may include epoxy resin and other components with a rigid structure. For example, in some embodiments, the core of the microcapsule also includes silicon dioxide. However, the cost of fumed silica with a smaller particle size is higher, and the particle size of ordinary silicon dioxide is larger, which affects the coating thickness. As a preferred embodiment of the present invention, the core of the microcapsule is composed of epoxy resin.

[0018] The method for forming microcapsules is not limited. In the embodiment of urea-formaldehyde resin coated epoxy resin, as preferred in the present invention, after adding epoxy resin to the prepolymer of urea-formaldehyde resin, adjusting the pH to 3-4, heating to 60-70°C for reaction for 2-4h, microcapsules are obtained. In the embodiment of lignin and urea-formaldehyde resin coated epoxy resin, as preferred in the present invention, lignin sulfonate is added during the preparation of the prepolymer of urea-formaldehyde resin; after adding epoxy resin to the prepolymer of lignin-modified urea-formaldehyde resin, adjusting the pH to 3-4, heating to 60-70°C for reaction for 2-4h, microcapsules are obtained. Among them, the pH can be 3, 3.5, 4, preferably 3; the temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, preferably 65°C; the reaction time can be 2h, 2.5h, 3h, 3.5h, 4h, preferably 3h.

[0019] Among the materials forming the coating, the choice of the binder is not limited. As a preference of the present invention, the binder is selected from at least one of ethylene-acrylic acid copolymer, polyethylene, polypropylene, starch, acrylate-polyurethane, and polyvinyl alcohol.

[0020] A specific binder combination can further improve the stiffness of the composite paper together with the microcapsules. In some embodiments, the binder includes ethylene-acrylic acid copolymer, polyethylene, and polypropylene. Polyethylene is used to provide barrier properties for the composite paper, polypropylene is used to improve the stiffness of polyethylene, and ethylene-acrylic acid copolymer is used to regulate the compatibility between polyethylene, polypropylene, microcapsules and wood powder. EAA has the characteristics of a ternary structure, and the carboxylic acid groups on it can react with hydroxymethyl, amino groups, etc. on urea-formaldehyde resin, and can also react with hydroxyl groups on wood powder, so that it can be inserted into a network structure with rigid support points, further improving the stiffness of the composite paper. At the same time, EAA contains polar groups and has high viscosity itself, which can play a role in toughening and bonding. In this embodiment, as a preferred embodiment of the present invention, the mass ratio of the ethylene-acrylic acid copolymer, polyethylene, and polypropylene is (20-30):10:(1-3). In terms of parts by mass, when polyethylene is 10 parts, ethylene acrylic acid copolymer (EAA) can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, and preferably 25 parts, and polypropylene can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, and preferably 2 parts.

[0021] In other embodiments, the binder includes ethylene-acrylic acid copolymer, polyethylene, and starch. Polyethylene is used to provide barrier properties for composite paper. In addition to being a binder, starch can also increase the shrinkage potential of paper matrix fibers through surface sizing to increase the elastic modulus and thus increase the stiffness of composite paper. Moreover, when starch is mixed with urea-formaldehyde resin, starch can cross-link with certain free formaldehyde in urea-formaldehyde resin, which can reduce the formaldehyde content of composite paper on the one hand, and on the other hand, the cross-linking effect can increase the connection between starch molecules and between starch and pulp fibers to strengthen the internal structure of composite paper and further improve the stiffness. Ethylene-acrylic acid copolymer has good blending properties with starch and polyethylene, which helps the compatibility of starch and polyethylene. In this embodiment, as a preferred embodiment of the present invention, the starch is thermoplastic enzymatic starch to reduce the volume and size of starch molecules, which is conducive to the entry of starch into the interior of the paper matrix. In this embodiment, as a preferred embodiment of the present invention, the mass ratio of ethylene-acrylic acid copolymer, polyethylene, and starch is (20-30):10:(5-15). In terms of mass parts, when polyethylene is 10 parts, the ethylene-acrylic acid copolymer can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, and preferably 25 parts; the starch can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, and preferably 10 parts.

[0022] The amount of coating on the paper substrate is not limited, but an appropriate amount can further improve the packaging performance of the composite paper. For example, too little amount may result in insufficient stiffness and bonding performance of the composite paper, while too much amount may result in too thick a coating on the composite paper, which may adhere to the small cigarette pack in the package during the heat sealing process, affecting the packaging effect. As a preferred embodiment of the present invention, the amount of the coating on the paper substrate is 5 to 8 g / m 2 , for example, it can be 5g / m 2 , 6g / m 2 , 7g / m 2 , 8g / m 2 , preferably 6g / m 2 .

[0023] Beneficial effects of the present invention:

[0024] 1. In the present application, wood powder in the paper matrix is ​​used, and the shell in the coating includes urea-formaldehyde resin and the core includes epoxy resin microcapsules, which are synergistically obtained to obtain a network structure with rigid support points, and the use of a binder helps the network structure with rigid support points to be evenly infiltrated in the paper matrix, thereby obtaining a paper-plastic composite paper with good stiffness.

[0025] 2. The composite paper of the present application can be used as cigarette box packaging paper. It has good stiffness and can ensure the regularity and three-dimensionality of the appearance of the box, and can better protect the small cigarette packs inside. DETAILED DESCRIPTION

[0026] The following are specific embodiments of the present invention, and further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0027] Example 1

[0028] A low-weight coated paper comprises a paper substrate and a coating disposed on one side of the paper substrate close to a packaging product. The materials forming the paper substrate include 85 parts of waste paper pulp and 15 parts of cationic modified wood powder by weight. The materials forming the coating include 7.5 parts of microcapsules and 92.5 parts of a binder by weight. The shell of the microcapsule includes urea-formaldehyde resin, the core includes epoxy resin, and the binder includes 62.5 parts of ethylene-acrylic acid copolymer, 25 parts of polyethylene, and 5 parts of polypropylene. The amount of the coating on the paper substrate is 6 g / m 2 .

[0029] This light weight coated paper is produced by the following steps:

[0030] S1. According to the mass parts, 100 parts of ordinary wood powder are added to the sodium hydroxide solution with a pH of 12, and then 15 parts of 3-chloro-2-hydroxypropyltrimethylammonium chloride are added, and after stirring evenly, the mixture is placed at 70°C for reaction for 4 hours. After the reaction is completed, the temperature is lowered, the mixture is filtered, and the solid matter is washed and filtered with anhydrous ethanol. The solid matter is naturally air-dried to obtain the cationic modified wood powder.

[0031] S2. The waste cardboard was broken into small pieces, soaked in deionized water for 24 hours, and pulped with a Wall-E pulper with a beating degree of 33°SR; the waste paper pulp was obtained by drying and placing in a sample bag overnight to balance the moisture.

[0032] S3. According to the mass ratio, 85 parts of waste paper pulp and 15 parts of cationic modified wood powder were mixed, and the mixture was dispersed with a pulp dispersing agent for 10 minutes to make the mixture uniform, and then the wet paper web was made. The wet paper web was then pressed at 0.8 MPa for 5 minutes. Finally, the wet paper web was dried at 105°C for 15 minutes to obtain a paper matrix. The basis weight of the paper matrix was 50 g / cm 2 , thickness is 70μm, tightness is 0.7g / cm 3 .

[0033] S4. According to the mass fraction, 5 parts of urea and 10 parts of formaldehyde solution with a volume fraction of 37% are mixed at room temperature until the urea is dissolved, and then triethanolamine is added to adjust the system pH to 9, and heated to 70°C for reaction for 1h to obtain a urea-formaldehyde resin prepolymer solution. After adding an emulsifier and water to the urea-formaldehyde resin prepolymer, 5 parts of ethyl acetate and 20 parts of epoxy resin are slowly added and emulsified for 30min. Then, the pH of the system is adjusted to 3 with sulfuric acid with a mass concentration of 10%, and heated to 65°C for 3h. Finally, it is cooled to room temperature, filtered and washed with deionized water, and dried to obtain microcapsules of urea-formaldehyde resin coated with epoxy resin.

[0034] S5. According to the mass parts, 7.5 parts of microcapsules, 62.5 parts of ethylene-acrylic acid copolymer, 25 parts of polyethylene, and 5 parts of polypropylene are mixed uniformly to obtain a mixture. The mixture is sent to a laminating machine, melted through a die head, and extruded onto a paper substrate, so that the mixture is melted into a film-like structure coating that is attached to the paper substrate. The amount of the coating on the paper substrate is 6g / m 2 .

[0035] Example 2

[0036] This embodiment is basically the same as Embodiment 1, the only difference being that the wood powder is ordinary wood powder.

[0037] Specifically: S3. According to the mass ratio, 85 parts of waste paper pulp and 15 parts of ordinary wood powder were mixed, and the mixture was dispersed by pulp dispersing agent for 10 minutes to make the mixture uniform, and then the wet paper web was made. Then the wet paper web was pressed at 0.8MPa for 5 minutes. Finally, it was dried at 105℃ for 15 minutes to obtain a paper matrix. The basis weight of the paper matrix is ​​50g / cm 2 , thickness is 70μm, tightness is 0.7g / cm 3 .

[0038] Example 3

[0039] This embodiment is basically the same as the embodiment 1, except that the shell of the microcapsule further includes lignin.

[0040] Specifically: S4. According to the mass fraction, 5 parts of urea, 10 parts of formaldehyde solution with a volume fraction of 37%, and 0.15 parts of lignin sulfonate are mixed at room temperature, and then triethanolamine is added to adjust the pH of the system to 9, and heated to 70°C for reaction for 1 hour to obtain a lignin-modified urea-formaldehyde resin prepolymer solution. After adding an emulsifier and water to the lignin-modified urea-formaldehyde resin prepolymer, 5 parts of ethyl acetate and 20 parts of epoxy resin are slowly added and emulsified for 30 minutes. Then, the pH of the system is adjusted to 3 with sulfuric acid with a mass concentration of 10%, and heated to 65°C for 3 hours. Finally, it is cooled to room temperature, filtered and washed with deionized water, and dried to obtain microcapsules of lignin and urea-formaldehyde resin coated with epoxy resin.

[0041] Example 4

[0042] This embodiment is basically the same as the embodiment 1, and the only difference is that the binder is different. The binder includes 51.5 parts of ethylene-acrylic acid copolymer, 20.5 parts of polyethylene, and 20.5 parts of thermoplastic enzymatic starch.

[0043] Specifically: Preparation of thermoplastic enzymatic starch: According to parts by mass, 30 parts of enzymatic starch, 4 parts of glycerol, and 4 parts of stearic acid are mixed and sent to a 75°C kneader for stirring for 10 minutes to obtain thermoplastic enzymatic starch. S5. According to parts by mass, 7.5 parts of microcapsules, 51.5 parts of ethylene-acrylic acid copolymer, 20.5 parts of polyethylene, and 20.5 parts of thermoplastic enzymatic starch are mixed evenly to obtain a mixture. The mixture is sent to a laminating machine, melted through a die head, and then extruded onto a paper substrate, so that the mixture is melted into a film-like structure coating that is attached to the paper substrate. The amount of the coating on the paper substrate is 6g / m 2 .

[0044] Example 5

[0045] This embodiment is substantially the same as the embodiment 1, except that the binder is different and includes 92.5 parts of ethylene-acrylic acid copolymer.

[0046] Specifically: S5. According to mass parts, 7.5 parts of microcapsules and 92.5 parts of ethylene-acrylic acid copolymer are mixed evenly to obtain a mixture. The mixture is melted and coated on a paper substrate. The amount of the coating on the paper substrate is 6 g / m 2 .

[0047] Example 6

[0048] This embodiment is basically the same as the embodiment 1, except that the materials forming the paper matrix include 95 parts by weight of waste paper pulp and 5 parts by weight of cationic modified wood powder.

[0049] Example 7

[0050] This embodiment is basically the same as the embodiment 1, except that the materials forming the paper matrix include 90 parts by weight of waste paper pulp and 10 parts by weight of cationic modified wood powder.

[0051] Example 8

[0052] This embodiment is basically the same as the embodiment 1, except that the materials forming the paper matrix include 80 parts by weight of waste paper pulp and 20 parts by weight of cationic modified wood powder.

[0053] Example 9

[0054] This embodiment is basically the same as the embodiment 1, except that the materials forming the paper matrix include 70 parts by weight of waste paper pulp and 30 parts by weight of cationic modified wood powder.

[0055] Example 10

[0056] This embodiment is basically the same as the embodiment 1, except that the materials forming the coating include, by weight, 1 part of microcapsules and 99 parts of a binder, wherein the binder includes 66.6 parts of ethylene-acrylic acid copolymer, 27 parts of polyethylene, and 5.4 parts of polypropylene.

[0057] Embodiment 11

[0058] This embodiment is basically the same as the embodiment 1, except that the materials forming the coating include 5 parts of microcapsules and 95 parts of a binder by weight, and the binder includes 64.4 parts of ethylene-acrylic acid copolymer, 25.5 parts of polyethylene, and 5.1 parts of polypropylene.

[0059] Example 12

[0060] This embodiment is basically the same as the embodiment 1, except that the materials for forming the coating layer include 10 parts of microcapsules and 90 parts of a binder by weight, and the binder includes 60.6 parts of ethylene-acrylic acid copolymer, 24.5 parts of polyethylene, and 4.9 parts of polypropylene.

[0061] Example 13

[0062] This embodiment is basically the same as the embodiment 1, except that the materials forming the coating include 15 parts of microcapsules and 85 parts of a binder by weight, and the binder includes 57.4 parts of ethylene-acrylic acid copolymer, 23 parts of polyethylene, and 4.6 parts of polypropylene.

[0063] Embodiment 14

[0064] This embodiment is basically the same as embodiment 1, the only difference is that the amount of coating on the paper substrate is 3g / m 2 .

[0065] Embodiment 15

[0066] This embodiment is basically the same as embodiment 1, the only difference is that the amount of coating on the paper substrate is 5g / m 2 .

[0067] Example 16

[0068] This embodiment is basically the same as embodiment 1, the only difference is that the amount of coating on the paper substrate is 8g / m 2 .

[0069] Embodiment 17

[0070] This embodiment is basically the same as embodiment 1, the only difference is that the amount of coating on the paper substrate is 10g / m 2 .

[0071] Application Examples

[0072] The composite papers obtained in Examples 1 to 17 were respectively used as wrapping papers for cigarette cartons.

[0073] Blank example

[0074] A paper substrate without wood powder was used as a blank example.

[0075] Specifically, 100 parts of waste paper pulp were de-slurried with a pulp de-slurry agent for 10 minutes to form a wet paper web. The wet paper web was then pressed at 0.8 MPa for 5 minutes. Finally, it was dried at 105°C for 15 minutes to obtain a paper matrix. The basis weight of the paper matrix was 50 g / cm 2 , thickness is 70μm, tightness is 0.7g / cm 3 .

[0076] Comparative Example 1

[0077] The paper substrate prepared in Example 1 is used as Comparative Example 1.

[0078] Comparative Example 2

[0079] The coating in Example 1 was coated on a paper substrate without wood powder to obtain a composite paper as Comparative Example 2.

[0080] Specifically, 100 parts of waste paper pulp were de-slurried with a pulp de-slurry agent for 10 minutes to form a wet paper web. The wet paper web was then pressed at 0.8 MPa for 5 minutes. Finally, it was dried at 105°C for 15 minutes to obtain a paper matrix. The basis weight of the paper matrix was 50 g / cm 2 , thickness is 70μm, tightness is 0.7g / cm 3 .

[0081] According to parts by mass, 7.5 parts of the microcapsules prepared in Example 1, 62.5 parts of ethylene-acrylic acid copolymer, 25 parts of polyethylene, and 5 parts of polypropylene were mixed uniformly to obtain a mixture. The mixture was sent to a laminating machine, melted through a die head, and then extruded onto a paper substrate, so that the mixture was melted into a film-like structure coating that was attached to the paper substrate. The amount of the coating on the paper substrate was 6 g / m 2 .

[0082] Comparative Example 3

[0083] A mixture of urea-formaldehyde resin, epoxy resin and binder was used as a coating material, and a film was applied on the paper substrate prepared in Example 1 to obtain a composite paper as Comparative Example 3.

[0084] Specifically, 3 parts of urea-formaldehyde resin, 4.5 parts of epoxy resin, 62.5 parts of ethylene-acrylic acid copolymer, 25 parts of polyethylene, and 5 parts of polypropylene are mixed evenly to obtain a mixture. The mixture is sent to a laminating machine, melted through a die head, and then extruded onto the paper substrate prepared in Example 1, so that the mixture is melted into a film-like structure coating that is attached to the paper substrate. The amount of the coating on the paper substrate is 6 g / m 2 .

[0085] Stiffness test

[0086] The composite paper obtained in the examples and comparative examples was tested for stiffness according to the constant speed bending method in the standard "GB / T 22364-2018 Determination of Bending Stiffness of Paper and Paperboard". The test results are shown in Table 1 below.

[0087] Table 1.

[0088]

[0089] As shown in Table 1, it can be seen from the comparison between Example 1 and the blank example that the present application uses wood powder in the paper matrix, adds a coating, and uses a binder and a microcapsule whose shell includes urea-formaldehyde resin and whose core includes epoxy resin in the coating, which can effectively improve the stiffness index of the composite paper, so that it can be used as cigarette box packaging paper. It can be seen from the comparison between Example 1, the blank example, Comparative Example 1 and Comparative Example 2 that although the use of wood powder alone in the paper matrix, or the use of a binder and a microcapsule whose shell includes urea-formaldehyde resin and whose core includes epoxy resin in the coating alone can provide the stiffness of the composite paper, the improvement rate of the stiffness is far less than the effect of using the two together. This may be because the wood powder in the paper matrix and the microcapsules in the coating can form a network structure with rigid support points, and this network structure can effectively improve the stiffness. It can be seen from the comparison between Comparative Example 3 that the urea-formaldehyde resin and the epoxy resin form a core-shell structure, and the improvement rate of the stiffness is obvious compared with the simple mixed use. This may be because the epoxy resin in the core-shell structure can more effectively become a support point.

[0090] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A low-weight coated paper, comprising a paper substrate and a coating disposed on at least one side of the paper substrate, characterized in that: The material forming the paper substrate includes wood powder; The materials forming the coating include microcapsules and a binder. The shell of the microcapsule includes urea-formaldehyde resin, and the core includes epoxy resin.

2. The low-weight coated paper according to claim 1, characterized in that: The amount of the wood powder added to the material forming the paper matrix is ​​10-20wt%.

3. The low-weight coated paper according to claim 1, characterized in that: The wood powder is cationized modified wood powder.

4. The low-weight coated paper according to claim 1, characterized in that: The amount of the microcapsules added to the material forming the coating is 5-10 wt %.

5. The low-weight coated paper according to claim 1, characterized in that: The shell of the microcapsule also includes lignin.

6. The low-weight coated paper according to claim 1, characterized in that: The binder is selected from at least one of ethylene-acrylic acid copolymer, polyethylene, polypropylene, starch, acrylate-polyurethane, and polyvinyl alcohol.

7. The low-weight coated paper according to claim 6, characterized in that: The binder includes ethylene-acrylic acid copolymer, polyethylene, and polypropylene.

8. The low-weight coated paper according to claim 6, characterized in that: The binder includes ethylene-acrylic acid copolymer, polyethylene, and starch.

9. The low-weight coated paper according to claim 1, characterized in that: The amount of the coating on the paper substrate is 3-20 g / m 2 .

10. Use of the low-weight coated paper according to any one of claims 1 to 9 in cigarette carton packaging.

Citation Information

Patent Citations

  • Coated paper

    CN117980561A